2019
DOI: 10.1021/acsomega.9b03130
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Severe Fever with Thrombocytopenia Syndrome Virus Based on Immunofluorescent Carbon Dots/SiO2 Nanosphere-Based Lateral Flow Assay

Abstract: Sensitive detection of severe fever with thrombocytopenia syndrome virus (SFTSV) by a point-of-care assay is of great significance for promoting clinical diagnosis. In this work, ultrasensitive detection of SFTSV was achieved by using fluorescent carbon dots/SiO2 nanospheres (CSNs) as reporters for a lateral flow assay. The prepared CSNs were resistant to extreme environments and had strong stability. The uniform CSNs with the size of about 200 nm were obtained by differential centrifugation. Their absolute qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…In another study, CDs@silica nanoparticles have been used to develop a lateral flow assay for detecting a severe fever with thrombocytopenia syndrome (SFTS), which has very similar symptoms to those of influenza. 215 As shown in Figure 7 B (.eft), the T line and C line on the nitrocellulose were modified by a selective antibody (SmAb) and nonselective antibody (i.e., goat antimouse IgG antibody), respectively. On the one hand, the positive results are shown as two bright lines under UV light (365 nm) ( Figure 7 B, right) when the sample diffuses through a capillary force in the lateral flow kit.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, CDs@silica nanoparticles have been used to develop a lateral flow assay for detecting a severe fever with thrombocytopenia syndrome (SFTS), which has very similar symptoms to those of influenza. 215 As shown in Figure 7 B (.eft), the T line and C line on the nitrocellulose were modified by a selective antibody (SmAb) and nonselective antibody (i.e., goat antimouse IgG antibody), respectively. On the one hand, the positive results are shown as two bright lines under UV light (365 nm) ( Figure 7 B, right) when the sample diffuses through a capillary force in the lateral flow kit.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…On the one hand, the positive results are shown as two bright lines under UV light (365 nm) ( Figure 7 B, right) when the sample diffuses through a capillary force in the lateral flow kit. 215 On the other hand, fluorophores with an aggregation-induced emission have also been used for detecting a virus. Kato et al reported the design of tetraphenylethylene-based oligosaccharide fluorescent probes for the detection of an influenza virus.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all those biomedical applications, fluorescence-based biosensing by leveraging their unique fluorescence properties has been extensively investigated for POC diagnostics of infectious diseases. For example, Xu et al [150] developed a fluorescent lateral flow assay using CDs/SiO 2 nanospheres (CSNs) as reporters for ultrasensitive POC detection of severe fever with thrombocytopenia syndrome virus (SFTSV). The fluorescent lateral flow assay owned good reproducibility, high specificity and sensitivity due to the excellent fluorescent properties of CSNs, and was able to achieve a low visual detection limit of as low as 10 pg mL −1 SFTSV nucleoprotein which was 2 orders of magnitude higher than that of the colloidal gold-based lateral flow test strip.…”
Section: Detection Methods For Poc Diagnostic Applicationsmentioning
confidence: 99%
“…Anti-SFTSV Abs were also immobilized at the TL to capture detected Ags, and GAM IgG Abs at the CL were used to capture remaining CDSNs. This device was evaluated, and the SFTSV detection results were consistent with PCR showing no cross-reactivity with HCG, AFP, CEA, CA125 [ 170 ]. In another research, Zuo and coworkers developed an LFA using Au NPs conjugated with anti-SFTSV mAbs as reporter probes.…”
Section: Viral Infections Determination Using Lfa Sensing Platformsmentioning
confidence: 99%